2010
DOI: 10.1016/j.jsps.2009.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Jasonia montana against ethinylestradiol-induced cholestasis in rats

Abstract: Estrogens, and particularly glucuronides such as ethinylestradiol (EE), have been shown to cause cholestasis in animal studies, by reducing bile acid uptake by hepatocytes. The aim of the present article is to investigate anticholestatic activity of the ethanolic extract of the aerial parts of Jasonia montana against liver cholestasis induced by EE in adult female rats in an attempt to understand its mechanism of action, which may pave the way for possible therapeutic applications. Subcutaneous administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 54 publications
6
24
0
Order By: Relevance
“…Hussein and Abdel-Gawad (2010) study greatly supported our results in this concern as they stated that BNO level is significantly depleted after J. montana treatment in rats-induced cholestasis. The high content of flavonoids and phenolic compounds in J. montana extract (Hussein and Abdel-Gawad, 2010) and J. Candicans (Hammerschmidt et al, 1993) may contribut in this effect.…”
Section: Biochemical Studysupporting
confidence: 90%
See 1 more Smart Citation
“…Hussein and Abdel-Gawad (2010) study greatly supported our results in this concern as they stated that BNO level is significantly depleted after J. montana treatment in rats-induced cholestasis. The high content of flavonoids and phenolic compounds in J. montana extract (Hussein and Abdel-Gawad, 2010) and J. Candicans (Hammerschmidt et al, 1993) may contribut in this effect.…”
Section: Biochemical Studysupporting
confidence: 90%
“…Moreover, Jasonia species could increase the activities of glutathione peroxidase (Gpx) and glutathione-s-transferase (GST) in the various tissues of rats (Hussein, 2008). Furthermore, Hussein and Abdel-Gawad, (2010) reported that Jasonia species extract effectively normalize the impaired antioxidant status in rats. The phenolic constituents sharing flavonoids in enhancing the total antioxidant capacity in Alzheimer's disease-treated rats.…”
Section: Biochemical Studymentioning
confidence: 99%
“…These compounds showed an inhibitory effect on serum TNF-α level in iron overload treated rats (Hussein and Farghaly, 2010). Also, Hussein and Abdel-Gawad (2010) reported that the flavonoids (or bioflavonoids) have the ability to suppress many types of transcription factors including TNF-α and H 2 O 2 as these natural compounds possess anti-inflammatory and antioxidant activities (Carlo et al, 1991;Rathee et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…[16] Diclofenac sodium has also been reported to suppress inflammation in experimental animal models. [17] As an extension of my interested research program in the extraction and therapeutic evaluation of medicinal plants, [18][19][20][21] I report herein, a facile route to calculate the median lethal doses (LD 50 ) and describe the anti-inflammatory effect of vicine and divicine isolated from fava beans (Vicia faba) which may pave the way for possible therapeutic application.…”
Section: Introductionmentioning
confidence: 99%